2017
DOI: 10.1039/c7ta06029g
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of anion-exchange membranes tethered with different hetero-cycloaliphatic quaternary ammonium hydroxides

Abstract: Quaternary ammonium (QA) cations with high alkaline stability are crucial for the long term performance of anion-exchange membrane (AEM) fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
121
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(127 citation statements)
references
References 48 publications
4
121
0
2
Order By: Relevance
“…Multiple publications on PPO-based AEMs have calculated IEC values from 1 H NMR spectra that are within 10% of the values determined via a titration method, another common technique for IEC determination. 45,[48][49][50] Membranes were fabricated by dissolving ImPPO-χ (0.3 g) in NMP (~5.5. g) at room temperature.…”
Section: Membrane Preparationmentioning
confidence: 99%
“…Multiple publications on PPO-based AEMs have calculated IEC values from 1 H NMR spectra that are within 10% of the values determined via a titration method, another common technique for IEC determination. 45,[48][49][50] Membranes were fabricated by dissolving ImPPO-χ (0.3 g) in NMP (~5.5. g) at room temperature.…”
Section: Membrane Preparationmentioning
confidence: 99%
“…Anion conductive polymers are used to compliment cation conductive polymer in dialysis or they can be used by themselves giving specific advantages . High ionic conductivity and chemical stability are universal goals which can be improved through phase segregation from a block copolymer structure . Block copolymers form efficient ion channels which confines the mobile hydroxide ion to ion conductive phase leading to better chemical stability, compared to random copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 High ionic conductivity and chemical stability are universal goals which can be improved through phase segregation from a block copolymer structure. [3][4][5][6][7] Block copolymers form efficient ion channels which confines the mobile hydroxide ion to ion conductive phase leading to better chemical stability, compared to random copolymers. Long alkyl side chains can improve the chemical stability of the tethered cation headgroup by facilitating ion channel formation.…”
mentioning
confidence: 99%
“…The excellent alkaline stability of spirocyclic QA cation was also confirmed by theoretical calculations . Based on their determination of alkaline stability of the small molecules, the aromatic polymers with pendent spirocyclic QA and piperidinium cations have been synthesized and used to prepare AEMs . Hickner's work indicated that the backbone of AEMs have effect on the alkaline stability of cations, and the AEM has aromatic backbone with ether groups is not stable in alkaline condition.…”
Section: Introductionmentioning
confidence: 86%
“…[34] Based on their determination of alkaline stability of the small molecules, the aromatic polymers with pendent spirocyclic QA and piperidi-nium cations have been synthesized and used to prepare AEMs. [34][35][36][37][38][39][40][41][42][43] Hickner's work indicated that the backbone of AEMs have effect on the alkaline stability of cations, [44] and the AEM has aromatic backbone with ether groups is not stable in alkaline condition. To date, there is few work on spirocyclic QAbased AEMs with an aliphatic backbone, and to understand the properties of this type of AEMs, a systematic study is needed.…”
Section: Introductionmentioning
confidence: 99%